Identification of Novel MicroRNAs Targeting SARS-CoV-2 through the Regulation of TMPRSS2/PI3K/AKT/PTEN Alignment in Lung Cancer: An in Silico Analysis - Mukhopadhyay, Debasmita (2021)
In this study, we investigated the interactions between SARS-CoV-2 and miRNAs associated with lung cancer using bioinformatic approaches. A special focus was placed on TMPRSS2 and lung cancer progression pathways involving AKT/RAS/PI3K/PTEN genes.